UMP undergraduates received 1Malaysia student discount card - UMP, PNC
A total of 7,737 Universiti Malaysia Pahang (UMP) undergraduates received the 1Malaysia Student Discount Card (KADS1M) which were distributed free to them so they could enjoy discounts of up to 60% at 231companies (2,414 outlets) nationwide.